Asset prices and wealth inequality in a simple model with idiosyncratic shocks - Salas, Sergio (Estudios de Economía, 2017)
This paper analytically solves a heterogeneous agent model with idiosyncratic shocks to marginal utility of consumption and explores the effects of the borrowing constraint on the price of the asset, the composition of borrowers and lenders in the credit market, and wealth inequality. Results are derived in a stylized model and in a pedagogical fashion.